An analysis of propositional knowledge from the perspective of Western and Islamic epistemology with special reference to Gettier’s counter-examples - Seyyed Mohsen Miri (حکمت اسرا)
The present article is composed of two parts. The first part begins with the traditional Western definition of propositional knowledge. While briefly touching the histrical roots of this definition and analyzing its three components, the article deals with Gettier’s counter- examples, bringing to light important responses presented by contemporary epistemologists. The second part of the article deals with the definition of propositional knowledge from the point of view of Muslim philosophers and sheds light on where this definition differs from the traditional Western one. It also touches on the division of knowledge into concept and proposition, expounding aspects of certain propositional knowledge and its characteristics. It concludes by showing that Gettier’s counter-examples do not harm the Islamic definition